Sustainable Indoor Lighting - Sansoni, Paola (Springer, 2015)
In Europe, energy consumption in the field of illumination represents a significant percentage of global consumptions. More generally, it is estimated that 14 % of electricity is used for lighting. It is therefore important to intervene in this sector not only because of the need to save energy but also for limiting light pollution and for reducing costs of maintenance. The improvement of lighting systems entails a multidisciplinary operation on all components, exploiting the results of techno logical progresses. Hence the design of lighting fixtures must take into account basically the amount of emitted light, but especially the mode of its distribution, avoiding to recover light rays in areas where they are not necessary. Concerning the light sources, these are rapidly evolving toward very high efficiency and long lifetime devices, with a view to bring down the replacement operation for faults and aging. The illumination system efficiency is also improved with targeted inter ventions on the electricity grid and on control systems and remote monitoring...